Yearbook of international trade statistics 1970 - 1971 - United Nations; United Nations (New York: United Nations, 1973)
The work covers world trade statistics containing detailed data for individual countries and basic summary tables showing, inter alia, the contribution of the trade of each country to the trade of its region and of the world, analyzing the flow of trade between countries and describing the fluctuations of the prices at which goods moved internationally.
rua 25/11/16
Ref.
Keywords: Commercial statistics; International trade